Do descriptive norms related to parents and friends predict fruit and vegetable intake similarly among 11-year-old girls and boys?. Issue 1 (9th October 2015) - Lehto, Elviira; Ray, Carola; Haukkala, Ari; Yngve, Agneta; Thorsdottir, Inga; Roos, Eva
Abstract: We examined whether there are sex differences in children's fruit and vegetable (FV) intake and in descriptive norms (i.e. perceived FV intake) related to parents and friends. We also studied whether friends' impact is as important as that of parents on children's FV intake. Data from the PRO GREENS project in Finland were obtained from 424 children at the age 11 years at baseline. At baseline, 2009 children filled in a questionnaire about descriptive norms conceptualised as perceived FV intake of their parents and friends. They also filled in a validated FFQ that assessed their FV intake both at baseline and in the follow-up in 2010. The associations were examined with multi-level regression analyses with multi-group comparisons. Girls reported higher perceived FV intake of friends and higher own fruit intake at baseline, compared with boys, and higher vegetable intake both at baseline and in the follow-up. Perceived FV intake of parents and friends was positively associated with both girls' and boys' FV intake in both study years. The impact of perceived fruit intake of the mother was stronger among boys. The change in children's FV intake was affected only by perceived FV intake of father and friends. No large sex differences in descriptive norms were found, but the impact of friends on children's FV intake can generally be considered as important as that of parents. Future interventions could benefit from taking into account friends' impact as role models on children's FV intake.